A Short Review on Machining With Ultrasonic MQL Method. Issue 1 (March 2020) - Katna, Rahul; Agrawal, Narayan; Suhaib, M.
Abstract: Cutting fluids are required in huge amount in the modern machining methods. Cutting fluids are needed for providing lubrication as well as cooling the workpiece during machining. Cutting fluids are made of mineral oils and have many drawbacks including many health hazards and environment impact. Various other methods of cutting fluid delivery are being tested in order to reduce the effects of cutting fluids in machining. One such method is minimum quantity lubrication. Many researchers have shown the effectiveness of MQL over the conventional flood method. However the MQL method has drawbacks in terms of heat carrying capacity. In order to increase the effectiveness of the MQL method many advanced methods are being tested for improving the cooling efficiency of the MQL method. One of the methods is ultrasonic method. This method is currently in nascent stages and is being researched upon as a viable alternative to the conventional MQL method. This paper describes this hybrid delivery method in machining.